Determination severity of pneumonia and responses of heat shock protein-70 concentration in vaccinated and non-vaccinated pneumonic goats - Dharshini Maslamary (2018)
Pneumonic pasteurellosis is the second most important infectious disease in small ruminant caused by Pasteurella multocida or Mannheimia haemolytica serotype A2, A7 and A9. Heat shock protein (HSP) such as HSP-70 is a major stressed-induced proteins that play a key role a destruction of pathogen and increase host resistance to chemical stresses. HSP-70 is a molecular chaperone that can be a vital biomarker in the diagnosis of bacterial diseases in small ruminant. Previous studies of pneumonic pasteurellosis have not dealt with the severity of pneumonia and responses of heat shock protein-70 in vaccinated and non-vaccinated pneumonic and non-pneumonic goat. Therefore, this study was designed where total of 76 goats (30 vaccinated and 46 non-vaccinated) were selected from four small ruminant farms. The animals were grouped into three groups namely normal vaccinated and non-vaccinated, vaccinated pneumonic group and non-vaccinated pneumonic group based on the clinical examination. Severity of pneumonia was determined based on the lung auscultation scoring and the severity was categorized as mild, moderate and severe. Blood samples were collected from these goats and the samples were subjected for goat HSP-70 analyses using ELISA technique. The findings showed that HSP-70 concentration is higher in non-vaccinated pneumonic goats than in vaccinated pneumonic goats. The HSP-70 concentration increased by 25% in vaccinated pneumonic goat and 45% in non-vaccinated pneumonic goats compared to the normal goats. However, the statistical analysis revealed that there is no significant difference (P>0.05) in the concentration of HSP-70 between vaccinated and non-vaccinated pneumonic goats. The severity of clinical signs revealed that non-vaccinated goats showed 50% more severe pneumonia clinical signs compared to vaccinated pneumonic goats. Statistically there was significant difference (P <0.05) in the severity of clinical signs of pneumonia between vaccinated and non-vaccinated pneumonic goats. In conclusion, the present study highlight that HSP-70 concentration were elevated slightly in non-vaccinated pneumonic goats compared to the vaccinated pneumonic goats. In general, less severe clinical signs and low concentration of HSP-70 in vaccinated goats showed that vaccinated goats had a better immunity and protections against pneumonia infection.
Also available in CD-ROM format.
Project paper (D.V.M) - Universiti Putra Malaysia, 2018.